Epidermal multinucleated giant cells are not always a histopathologic clue to a herpes virus infection: multinucleated epithelial giant cells in the epidermis of lesional skin biopsies from patients with acantholytic dermatoses can histologically mimic a - Philip R. Cohen (Mattioli1885, 2014)
Background: Multinucleated giant cells in the epidermis can either be epithelial or histiocytic. Epithelial multinucleated giant cells are most often associated with herpes virus infections.